2010
DOI: 10.1016/s1684-1182(10)60026-6
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M Type Extended Spectrum β-Lactamases in Escherichia coli Isolates From Community Acquired Upper Urinary Tract Infections at a University in the European Part of Turkey

Abstract: Extended spectrum beta-lactamase (ESBL) producing Escherichia coli has been an emerging etiologic agent in the community acquired infections. We investigated the occurrence of ESBL producing E. coli isolated from patients admitted with community acquired urinary tract infection (UTI) to the hospital of the Trakya University, Turkey during 2006. Eleven single patient isolates of E. coli harboring ESBL were identified among 30 E. coli isolated from patients admitted with symptoms corresponding to upper UTI. CTX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…Only at the level of academic research at the Universities, this subject is recently under study. In comparison with neighboring countries, this high percent of ESBL production noted in this study, is in agreement with what is found in Iran where 56% [21] of E. coli isolates were ESBL producers, and in Turkey where 74.6% [22] of E. coli isolates from hospitalized patients, and 36.7% of isolates from outpatients [23] were ESBL producers. While it is higher than that noted in Arab Gulf countries, such as Saudi Arabia [24] and Kuwait [25] (10% and 26% of hospital isolates, respectively, and 4% and 12% of community isolates, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Only at the level of academic research at the Universities, this subject is recently under study. In comparison with neighboring countries, this high percent of ESBL production noted in this study, is in agreement with what is found in Iran where 56% [21] of E. coli isolates were ESBL producers, and in Turkey where 74.6% [22] of E. coli isolates from hospitalized patients, and 36.7% of isolates from outpatients [23] were ESBL producers. While it is higher than that noted in Arab Gulf countries, such as Saudi Arabia [24] and Kuwait [25] (10% and 26% of hospital isolates, respectively, and 4% and 12% of community isolates, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Our results revealed that the ESBL-producing E. coli rate was 50.5% in patients with community-onset UTI, and 63.6% of ESBL (+) patients were diagnosed as having healthcare-associated UTIs, while only 29% of ESBL (-) patients had healthcare-associated UTIs. This prevalence seems to be higher than in previous studies [3,14]. In a study from Turkey, the SMART study, the rate of ESBLpositive E. coli was much higher in healthcare-associated than community-acquired UTIs during 2011 and 2012, at 50% and 38%, respectively [14].…”
Section: Discussionmentioning
confidence: 65%
“…For example, in a recent study in Saudi Arabia [24], 20.3% of UPEC isolates from hospitalized patients were ESBL producers. Reports from Egypt, Iran, and Turkey revealed that the distribution of ESBL-EC was 78.8% [25], 56% [26], and 36.7% [27], respectively. In a study that comprised 22 European countries for the period of 2004 to 2007, the rate of ESBL-EC was 9.8% [5], while in a more recent study, it varied from 2% to 8% [28].…”
Section: Discussionmentioning
confidence: 99%